Cerebrospinal Fluid Leak After Septoplasty in Crouzon Syndrome. Issue 1 (January 2021) - Demir, Berat; Abuzaid, Ghazi; Binnetoglu, Adem
Abstract : Abstract: Crouzon syndrome presents with craniofacial deformities due to early fusion of cranial sutures. Deviation of the nasal septum could be seen clinically in Crouzon syndrome. Cerebrospinal fluid leaks (CSF) after septoplasty are extremely rare and typically present with simple rhinorrhea, meningitis, and pneumocephalus. Herein, we report an adult patient with Crouzon syndrome who experienced CSF complication after septoplasty surgery. Supplemental Video: CSF leak repair operation, http://links.lww.com/SCS/B930 Abstract : Supplemental Digital Content is available in the text